Chemical bath deposition of single crystal SnS nanobelts on glass substrates. (August 2018) - Cao, Meng; Wu, Chuangsheng; Yao, Kefeng; Jing, Jiahe; Huang, Jian; Cao, Meng; Zhang, Jijun; Lai, Jianming; Ali, Omar; Wang, Linjun; Shen, Yue
Graphical abstract: Highlights: Single crystal SnS nanobelts were deposited by CBD method. The morphologies of SnS nanobelts were regulated by mole ratios of precursors and pH levels. The photo-electrical properties of SnS nanobelts were characterized. Abstract: SnS nanobelt thin films were deposited on glass substrates in acidic solution by chemical bath deposition (CBD) method. The belt-like morphologies of as-deposited SnS thin films were characterized by scanning electron microscope (SEM) and transmission electron microscopy (TEM). X-ray diffraction (XRD) and Raman measurements were carried out to confirm the crystal structures and phase purities of SnS nanobelt thin films. The morphologies and phase purities of SnS thin films were influenced greatly by the tin and sulfur precursors. The bandgaps of SnS nanobelts were determined to be 1.39–1.41 eV by UV–vis absorption and photoluminescence (PL) spectra. Current-voltage ((IV)) and current-time ((I-T)) characteristics were studied to demonstrate the photoelectric performances of SnS nanobelt thin films.